1999
DOI: 10.1111/j.1349-7006.1999.tb00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Wakame Seaweed Suppresses the Proliferation of 7,12‐Dimethylbenz(a)‐anthracene‐induced Mammary Tumors in Rats

Abstract: We examined the anti-tumor proliferation effects of wakame seaweed on 7,12-dimethylbenz(a)-anthracene (DMBA)-induced rat mammary tumor. DMBA was administered to 8-week-old female Sprague-Dawley rats, and rats which developed mammary tumors were assigned randomly to three groups. Commercial rat feed was used in a control group (group I-A), and two feed mixtures were prepared, which contained commercial rat feed blended with wakame at 1.0% (group I-B) and 5.0% (group I-C) by weight. The respective feeds were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
69
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 14 publications
3
69
0
4
Order By: Relevance
“…Miyeok intake did not show any significant associations with the risk of breast cancer in the present study, a finding which may be due to the low consumption frequency and low variation in miyeok intake among the subjects. However, U. pinnatifida (miyeok) has been reported to suppress mammary tumour growth in rats (25) , while fucoidan and fucoxanthin from U. pinnatifida has antitumour (39,40) and antioxidant activities (41) . Therefore, further studies are needed to investigate the relationship between miyeok intake and breast cancer risk in other research settings including areas with a large variation of miyeok intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyeok intake did not show any significant associations with the risk of breast cancer in the present study, a finding which may be due to the low consumption frequency and low variation in miyeok intake among the subjects. However, U. pinnatifida (miyeok) has been reported to suppress mammary tumour growth in rats (25) , while fucoidan and fucoxanthin from U. pinnatifida has antitumour (39,40) and antioxidant activities (41) . Therefore, further studies are needed to investigate the relationship between miyeok intake and breast cancer risk in other research settings including areas with a large variation of miyeok intake.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine acts as an antioxidant and antiproliferative agent, which contributes to the integrity of the normal mammary gland (44) . The addition of seaweeds (Laminaria, Porphyra tenera and wakame: miyeok) to the diet and iodine supplement showed a suppressive effect on the development and size of both benign and cancer neoplasias in animal studies (10,25,45,46) . Taken together, these results indicate that the protective effect of gim on the risk of breast cancer may be attributed to the antioxidant and antitumour activities of gim components such as polysaccharides, protein, polyphenol, carotenoids (16) , chlorophyll (16) and iodine, etc.…”
Section: Discussionmentioning
confidence: 99%
“…We have been studying the relationship between iodine and breast cancer for 10 years, trying to determine whether iodine is useful for chemoprevention of breast cancer. [6][7][8] There have been several reports on the relationship of iodine and breast cancer, [9][10][11] but the present paper is the first concerning breast cancer chemoprevention by seaweed.…”
mentioning
confidence: 99%
“…However, this dose, if scaled up to the human body weight, is too large to be practicable. 8) In the present experiments, mekabu was used instead of wakame. It contained almost the same amount of iodine as the wakame used in our former experiments (5.9 vs. 5.7 mg/100 g), but is cheaper and easier to process than wakame.…”
mentioning
confidence: 99%
“…In an earlier study, we and others reported that dietary seaweed delayed the time to tumor onset in a rat dimethylbenzanthracene mammary-induced cancer model (3)(4)(5)(6)(7). In preparation for a clinical study in humans, it was necessary to evaluate common edible seaweeds for iodine content since excess iodine intake might adversely affect thyroid function.…”
mentioning
confidence: 99%